Therapy Contamination as a Measure of Therapist Treatment Adherence in a Trial of Cognitive Behaviour Therapy versus Befriending for Psychosis. Issue 3 (29th October 2013) - Bendall, Sarah; Allott, Kelly; Jovev, Martina; Marois, Marie-Josee; Killackey, Eoin J.; Gleeson, John F.; Alvarez-Jimenez, Mario; McGorry, Patrick D.; Jackson, Henry J.
Abstract : Background: High quality randomized controlled trials (RCT) of psychotherapeutic interventions should ensure that the therapy being tested is what is actually delivered. However, contamination of one therapy into the other, a critical component of treatment adherence, is seldom measured in psychotherapy trials of psychosis.Aims: The aim of the study was to determine whether a purpose-designed measure, the ACE Treatment Integrity Measure (ATIM) could detect therapy contaminations within a controlled trial of cognitive behavioural therapy (CBT) versus Befriending for first-episode psychosis and to compare the ATIM to a more traditional adherence measure, the Cognitive Therapy Scale (CTS).Method: Therapy sessions were audio-recorded and at least one therapy session from 53 of the 62 participants in the RCT was rated by an independent rater using the CTS and ATIM.Results: Ninety-nine therapy sessions were rated. All Befriending sessions and all but three CBT sessions were correctly identified. The ATIM showed that 29 of the 99 (29%) sessions were contaminated by techniques from the other therapy. Within the CBT sessions, 19 of the 51 sessions (37%) were contaminated by one or more Befriending techniques. Of the Befriending sessions, 10 of 48 (21%) were contaminated by ACE techniques. The mean CTS score was higher in the CBT than the Befriending group.Conclusions: The ATIM was able to detect contaminations and revealed more meaningful, fine-grained analysis of what therapy techniques were being delivered and what contaminations occurred. The study highlights the benefit of employing purpose-designed measures that include contamination when assessing treatment adherence.